(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
The issue of delayed cancer diagnoses remains apparent during a time when healthcare services expand, and digital connectivity permeates the healthcare system. Although modern technology and increased healthcare resources have emerged, diagnosis delays continue to be a crucial challenge across healthcare settings. The research highlights that these delays arise from various factors, including personal and cultural dimensions, as well as systemic and structural issues. The interplay of health literacy deficits, economic insecurity, reliance on non-professional caregivers, and insufficient primary care support contributes to this ongoing problem. A comprehensive solution necessitates a whole-system approach that integrates community-based strategies with system-wide collaboration. Enhancements in public health education, coupled with improved primary care training, digital health integration, and financial support, will foster environments that accelerate cancer detection and treatment, ultimately leading to better patient outcomes. Achieving timely and effective cancer care for all entails ongoing cooperation among healthcare providers, policymakers, and community members to address these challenges, irrespective of socioeconomic status.